Representations of Silvio Berlusconi on YouTube : identification within a supra-logic of entertainment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Communication at Massey University, Wellington, New Zealand - Ross, Michael Robert (Massey University, 2012)
This thesis addresses the prevalence of the logics of entertainment and celebrification in a sample of political discourse on internet file-sharing website YouTube. Drawing inspiration from Postman's (1986) account of entertainment's dominance of broadcast television, it attempts to transfer the essence of his critique to the medium of YouTube. Through employing a content analysis methodology that attempts to transcend traditional quantitative and qualitative distinctions (Krippendorff, (2004), the study examines the extent to which entertainment logics structure representations of former Italian Prime Minister Silvio Berlusconi on YouTube. It also draws on the concept of 'celebrity politician typologies' (West & Orman, 2002; Street, 2004), in an attempt to evaluate Berlusconi's representation on YouTube through an established set of celebrity 'traits'. This idea of 'celebrity politician typologies' is supplemented through the use of 'Burkean identification' (1958), in order to better understand how audiences articulate identification or disidentification with the controversial figure of Berlusconi. This thesis finds the YouTube representation of Silvio Berlusconi to be a discourse dominated by the logics of entertainment and celebrification. It also finds that Berlusconi's celebrity appears to transcend the boundaries of the existing 'celebrity politician typologies'. The application of Burkean identification reveals that, in some instances, Berlusconi appears to inspire a paradoxical form of identification; one in which YouTube users cognitively disidentify with him as a politician, yet display a degree of identification with him as an entertainer. The study concludes that Berlusconi's representation on YouTube demonstrates an audience internalisation, and even amplification, of the entertainment logics that Postman (1986) claimed structured political discourses in the broadcast television era.
Keywords: Celebrification; YouTube; Silvio Berlusconi; Politics and culture; Celebrities and mass media; Media representation